2016
DOI: 10.1007/978-3-319-22461-9_1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetics and Conservation Biology: Drawing a Path into the Diversity of Life

Abstract: In the midst of a major extinction crisis, the scientifi c community is called to provide criteria, variables and standards for defi ning strategies of biodiversity conservation and monitoring their results. Phylogenetic diversity is one of the variables taken in account. Its consideration in biodiversity conservation stemmed from the idea that species are not equal in terms of evolutionary history and opened a completely new line of investigation. It has turned the focus to the need of protecting the Tree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 88 publications
0
7
0
4
Order By: Relevance
“…Phylogenetic approaches have become a pivotal tool for studying evolutionary dynamics and implementing more effective conservation plans in diverse ecosystems world‐wide (Frishkoff et al., 2014; Hughes et al., 2020; Pellens & Grandcolas, 2016). However, studies targeting the phylogenetic responses of species assemblages to the temporal dynamics of matrix regeneration in human‐dominated landscapes are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic approaches have become a pivotal tool for studying evolutionary dynamics and implementing more effective conservation plans in diverse ecosystems world‐wide (Frishkoff et al., 2014; Hughes et al., 2020; Pellens & Grandcolas, 2016). However, studies targeting the phylogenetic responses of species assemblages to the temporal dynamics of matrix regeneration in human‐dominated landscapes are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the African Cyprinidae represents more than 13 Gy of PD, and that if all currently threatened species slide to extinction, we would lose ϳ5 Gy of PD, representing ϳ37% of total PD of African Cyprinidae. The loss of 37% of total PD is illafforded in the context of multiple and persistent calls to preserve evolutionary diversity rather than just species richness (Jetz et al 2004;Pellens and Grandcolas 2016). These calls are motivated by increasing evidence that preserving evolutionary diversity is necessary to maintain the diversity of ecosystem functions (Forest et al 2007;Veron et al 2017), the conservation of rare and unique species (Faith 1992;Winter et al 2012), and, more critically, for the maintenance of a sustainable delivery of known and hidden goods and services (Forest et al 2007;Faith 2008;Faith et al 2010;Faith and Polloc 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This is a complex topic, with various views held on the most appropriate way to assess and conserve phylogenetic diversity (e.g., papers in Pellens and Grandcolas, 2016a). The definition of phylogenetic diversity may vary, but in the most general sense it refers to differences among organisms resulting from their evolutionary history, with the diversity contained within a phylogeny (Pellens and Grandcolas, 2016b). For those who favor using phylogenetic diversity as a conservation guideline, the basic idea is that it is important to conserve the widest range of diversity in terms of traits generated by evolution within a species or within lineages consisting of two or more taxa.…”
Section: Molecular Markersmentioning
confidence: 99%